2020
DOI: 10.3390/medicina56060295
|View full text |Cite
|
Sign up to set email alerts
|

Who Consult an Adult Psychiatric Emergency Department? Pertinence of Admissions and Opportunities for Telepsychiatry

Abstract: Background and Objectives: Psychiatric disorders constitute frequent causes of emergency department (ED) admissions and these rates are increasing. However, referring to ED a whole range of conditions that could or should be dealt with elsewhere is imposing itself as a problematic situation. We aimed: (1) to provide a descriptive picture of the socio-demographic and diagnostic characteristics of the visits among adults at the psychiatric ED; (2) to estimate the clinical pertinence of these visits. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
0
34
1
3
Order By: Relevance
“…Similar to the scarcity of data on SI and SB in patients with comorbid illness [32][33][34], fairly little is known about the association between CTE and suicidality to date. Thus, the primary objective of this report is to describe the occurrence of severe suicidality in two retired contact sports professionals who exhibited CTE.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the scarcity of data on SI and SB in patients with comorbid illness [32][33][34], fairly little is known about the association between CTE and suicidality to date. Thus, the primary objective of this report is to describe the occurrence of severe suicidality in two retired contact sports professionals who exhibited CTE.…”
Section: Introductionmentioning
confidence: 99%
“…Although these measures are needed to protect physical health, the psychological impact of the pandemic is still emerging. To alleviate the concerns surrounding mental health, there has been a growing interest in telepsychiatry, which is defined as "the delivery of mental health care in the form of live and interactive videoconferencing'' [3]. Telepsychiatry has proven to be an effective approach for helping people access mental health services in remote and underserved areas [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing measures, such as isolation and social distancing, have separated people from their loved ones, leading to loneliness, boredom, and stress. Recent mental health studies on COVID -19 have revealed that these feelings are associated with common mental health disorders, such as depression and anxiety [6][7][8], and that the most vulnerable are those with preexisting mental health disorders [3][4][5]. Moreover, emerging evidence has suggested that the environmental nature of public health measures (eg, locations where quarantine is carried out) can lead to different effects on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidality covers a host of phenomena, ranging from suicidal ideation (SI) to suicidal behaviors (SB), which include suicide attempts (SA), as well as completed suicide [ 1 ]. In spite of its seriousness, data on the prevalence of suicidality in individuals with a pre-existing illness [ 2 , 3 , 4 ], especially conditions with a neurological origin such as brain tumors, have not been frequently reported [ 5 , 6 ]. In this study, we provide a concise synthesis of the literature on this topic in order to summarize the reported frequency of SI and SB in patients with brain tumors.…”
Section: Introductionmentioning
confidence: 99%